Early Mechanical Alterations in Phospholamban Mutation Carriers - Taha, Karim; te Rijdt, Wouter P.; Verstraelen, Tom E.; Cramer, Maarten J.; de Boer, Rudolf A.; de Bruin-Bon, Rianne H.A.C.M.; Bouma, Berto J.; Asselbergs, Folkert W.; Wilde, Arthur A.M.; van den Berg, Maarten P.; Teske, Arco J. (JACC. Cardiovascular imaging, 2021)
This study aimed to explore echocardiographic characteristics of phospholamban (PLN) p.Arg14del mutation carriers to investigate whether structural and/or functional abnormalities could be identified before onset of symptoms. Carriers of the genetic PLN p.Arg14del mutation may develop arrhythmogenic and/or dilated cardiomyopathy. Overt disease is preceded by a pre-symptomatic phase of variable length in which disease expression seems to be absent. PLN p.Arg14del mutation carriers with an available echocardiogram were included. Mutation carriers were classified as pre-symptomatic if they had no history of ventricular arrhythmias (VAs), a premature ventricular complex count of <500/24 h, and a left ventricular (LV) ejection fraction of ≥45%. In addition, we included 70 control subjects with similar age and sex distribution as the pre-symptomatic mutation carriers. Comprehensive echocardiographic analysis (including deformation imaging) was performed. The final study population consisted of 281 PLN p.Arg14del mutation carriers, 139 of whom were classified as pre-symptomatic. In comparison to control subjects, pre-symptomatic mutation carriers had lower global longitudinal strain and higher LV mechanical dispersion (both p < 0.001). In addition, post-systolic shortening (PSS) in the LV apex was observed in 43 pre-symptomatic mutation carriers (31%) and in none of the control subjects. During a median follow-up of 3.2 years (interquartile range: 2.1 to 5.6 years) in 104 pre-symptomatic mutation carriers, nonsustained VA occurred in 13 (13%). Presence of apical PSS was the strongest echocardiographic predictor of VA (multivariable hazards ratio: 5.11; 95% confidence interval [CI]: 1.37 to 19.08; p = 0.015), which resulted in a negative predictive value of 96% (95% CI: 89% to 98%) and a positive predictive value of 29% (95% CI: 21% to 40%). Global and regional LV mechanical alterations in PLN p.Arg14del mutation carriers precede arrhythmic symptoms and overt structural disease. Pre-symptomatic mutation carriers with normal deformation patterns in the apex are at low risk of developing VA within 3 years, whereas mutation carriers with apical PSS appear to be at higher risk. [Display omitted]